Penggunaan Sampah Daur Ulang sebagai Media Pembelajaran Matematika di SMP Bireuen - Zulfikar, Zulfikar; Ismi, Khairul (Jurnal Ilmiah Guru Madrasah, 2025)
This study aims to develop recycled waste-based learning media to understand number concepts and mathematical operations at the junior high school level. The waste used consists of plastic waste, cardboard, and bottle caps, which are processed into innovative and contextual learning aids. In general, recycled waste can reduce environmental pollution, extend the useful life of materials, and provide economic and educational value if used creatively. The study was conducted at several junior high schools in Bireuen District using a descriptive qualitative approach. The results of the study indicate that the use of recycled materials as learning media increases students' interest in learning, understanding of number concepts, and computational skills. Additionally, this approach also instils environmental awareness and creative skills. This strategy is effective as an alternative to contextual learning that is both enjoyable and meaningfu